Chitotriosidase as biomarker for early stage amyotrophic lateral sclerosis: a multicenter study - Steinacker, Petra; Feneberg, Emily; Halbgebauer, Steffen; Witzel, Simon; Verde, Federico; Oeckl, Patrick; Van Damme, Philip; Gaur, Nayana; Gray, Elizabeth; Großkreutz, Julian; Jardel, Claude G.; Kachanov, Mykyta; et al. (Amyotrophic lateral sclerosis & frontotemporal degeneration, 2021)
Amyotrophic lateral sclerosis; chitotriosidase; neurofilaments; prognostic biomarker